The Role of Juvenile Hormone during Immune Response in Drosophila melanogaster - Tschernuth, Sebastian (Jihočeská univerzita, 2020)
The role of Juvenile hormone during immune response was investigated in Drosophila melanogaster larvae. The levels of Juvenile hormone were measured directly by mass spectrometry and indirectly by monitoring Krüppel Homologue expression. Neither of those approaches were successful. We genetically manipulated JH production and signalling, infected the larvae with parasitoid wasps and found a significant difference in immune strength between larvae with and without functional JH production.
The Role of Juvenile Hormone during Immune Response in Drosophila melanogaster
Keywords: Juvenile Hormone; Immune Response; Drosophila melanogaster; Genetics; Juvenile Hormone; Immune Response; Drosophila melanogaster; Genetics